1994
DOI: 10.1210/jc.79.4.934
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic-pituitary-adrenal axis activation and stimulation of systemic vasopressin secretion by recombinant interleukin-6 in humans: potential implications for the syndrome of inappropriate vasopressin secretion

Abstract: We recently demonstrated that sc administered interleukin-6 (IL-6) strongly stimulates the human hypothalamic-pituitary-adrenal (HPA) axis, with mild toxicity and no hypotensive effects. In this study, we evaluated the response of the human HPA axis to escalating iv doses of recombinant IL-6 in six patients with cancer and good performance status who received daily, every 8 h, three equal doses of 0.3-30 micrograms/kg IL-6. The plasma levels of IL-6 assayed by a specific enzyme-linked immunosorbent assay durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
83
1
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(89 citation statements)
references
References 0 publications
4
83
1
1
Order By: Relevance
“…LPS-induced vasopressin release was shown to be independent of known stimuli, including serum osmolality, and hemodynamic changes [15]. Interestingly, vasopressin secretion was also stimulated by intravenous injection of IL-1β in rats [16], by intracerebroventricular injection of IL-6 in rats [17] and, most notably, by intravenous injection of IL-6 in humans [18]. Similarly, oxytocin secretion was stimulated by the administration of LPS or IL-1β [19].…”
Section: Cytokine-induced Vasopressin Releasementioning
confidence: 99%
See 1 more Smart Citation
“…LPS-induced vasopressin release was shown to be independent of known stimuli, including serum osmolality, and hemodynamic changes [15]. Interestingly, vasopressin secretion was also stimulated by intravenous injection of IL-1β in rats [16], by intracerebroventricular injection of IL-6 in rats [17] and, most notably, by intravenous injection of IL-6 in humans [18]. Similarly, oxytocin secretion was stimulated by the administration of LPS or IL-1β [19].…”
Section: Cytokine-induced Vasopressin Releasementioning
confidence: 99%
“…Mastorakos et al [18] showed that in these patients the administration of IL-6 resulted in a fast dose-dependent rise in vasopressin concentration (to 15.6 pg/ml, normal range ∼1–4 pg/ml). Importantly, IL-6 treatment did not influence TNF-α or IL-1β concentrations, suggesting that vasopressin release by IL-6 can occur independently of its associated cytokines.…”
Section: Clinical Examples Of Hyponatremia and Inflammationmentioning
confidence: 99%
“…Despite its inherent inflammatory activity, IL-6 plays a major role in the overall control of inflammation, by stimulating glucocorticoid secretion [83, 84]and by suppressing the secretion of TNF-α and IL-1. Furthermore, catecholamines inhibit IL-12 and stimulate IL-10 secretion via β-adrenergic receptors, thereby causing suppression of innate and cellular immunity, and stimulation of humoral immunity [85].…”
Section: Effects Of Chronic Hyperactivation Of the Stress Systemmentioning
confidence: 99%
“…Activation of the HPA axis by proinflammatory cytokines provokes the release of glucocorticoids which, in turn, prevent the continuing immune-inflammatory response [1]and thereby regulates a homeostatic neuroendocrine-immune regulatory loop. For example, proinflammatory cytokines, such as interleukin 1β (IL-1β), interleukin 6 (IL-6), and tumor necrosis factor (TNF-α), are expressed in HPA axis tissues [2, 3, 4]and stimulate the release of corticotropin-releasing hormone (CRH), adrenocorticotropin (ACTH), and corticosterone [5, 6, 7, 8, 9, 10]. This indicates that proinflammatory cytokines play an important role in maintaining neuroendocrine-immune homeostasis through the HPA axis.…”
Section: Introductionmentioning
confidence: 99%